Stem cells derived from amniotic fluid and placenta - Atala, Anthony (Henry Stewart Talks, 2014)
Introduction to the amniotic fluid and placenta, Collecting stem cells from the amniotic fluid or placenta, Cell markers in amniotic fluid or placenta derived stem cells, Amniotic fluid or placenta derived stem cells are able to form embryoid bodies, Uses of amniotic fluid or placenta derived stem cells: Immunomodulation, Uses of amniotic fluid or placenta derived stem cells: Regenerative medicine, Amniotic fluid or placenta derived stem cells can be differentiated into a variety of cell types, Amniotic fluid stems cells in the kidney, Necrotizing enterocolitis; a model and treatment with amniotic fluid stems cells, Clinical uses of amniotic fluid or placenta derived stem cells